2020
DOI: 10.4102/koedoe.v62i1.1613
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation needs and preferences of visitors to Kgalagadi Transfrontier Park

Abstract: South African National Parks is one of South Africa’s main drawcards for ecotourists. One of these parks is the Kgalagadi Transfrontier Park (KTP), which is also a World Heritage Site (WHS). Because tourism is key to national parks and WHSs, visitor management strategies such as interpretation are vital for these destinations to provide tourists with better experiences and knowledge. The aim of this research was therefore to determine the interpretation needs and preferences of visitors to KTP. The factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To increase understanding staff performance and job satisfaction, researchers could expand the comparison of interpretation goals to include the agency’s legislation, policies, and management plans (Boswell, 2006), and to outcomes as reported by visitors (e.g., just after an interpretive experience and some time later) and as desired by visitors (Van der Merwe et al, 2020). Researchers should examine which factors affect the differences in priorities for interpretation goals and resources used (e.g., accountability, metrics, collaboration possibilities).…”
Section: Discussionmentioning
confidence: 99%
“…To increase understanding staff performance and job satisfaction, researchers could expand the comparison of interpretation goals to include the agency’s legislation, policies, and management plans (Boswell, 2006), and to outcomes as reported by visitors (e.g., just after an interpretive experience and some time later) and as desired by visitors (Van der Merwe et al, 2020). Researchers should examine which factors affect the differences in priorities for interpretation goals and resources used (e.g., accountability, metrics, collaboration possibilities).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, visitors in this study often expressed surprise that a coastal area that they had visited was a MPA. There is currently limited interpretation, or facilitated experiences, to support tourists’ learning in most South African protected areas (Van der Merwe et al, 2020) and recent research in the Aliwal Shoal MPA in South Africa highlighted an urgent need for interpretive signage to communicate with people visiting the MPA (Francolini et al, 2023). This signage should, at the very minimum, highlight the fact that the area is a MPA.…”
Section: Discussionmentioning
confidence: 99%
“…This has implications for communication about MPAs in general, and particularly amongst stakeholders such as tourists. Visitors to protected areas in South Africa consider learning to be an important motivation and it has been suggested that such protected areas should educate tourists through information boards, talks, videos, and displays (Kruger & Saayman, 2010; Van der Merwe et al, 2020). As management plans for MPAs are developed and implemented, it is recommended that these include a focus on effective communication.…”
Section: Discussionmentioning
confidence: 99%